2017
DOI: 10.1007/s10545-017-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for lysosomal storage disorders: recent advances for metachromatic leukodystrophy and mucopolysaccaridosis I

Abstract: Lysosomal storage diseases (LSDs) are rare inherited metabolic disorders characterized by a dysfunction in lysosomes, leading to waste material accumulation and severe organ damage. Enzyme replacement therapy (ERT) and haematopoietic stem cell transplant (HSCT) have been exploited as potential treatments for LSDs but pre-clinical and clinical studies have shown in some cases limited efficacy. Intravenous ERT is able to control the damage of visceral organs but cannot prevent nervous impairment. Depending on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 82 publications
1
49
0
Order By: Relevance
“…We provide evidence to focus on therapies that can target the microglial population, such as gene therapy and haematopoietic stem cell transplantation. These therapies are already being used in clinical trials for LSDs and other types of leukodystrophies (Penati et al, 2017;Ohashi, 2019;Schiller et al, 2019) and could therefore be adapted to treat children suffering from RNAseT2-deficient leukoencephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…We provide evidence to focus on therapies that can target the microglial population, such as gene therapy and haematopoietic stem cell transplantation. These therapies are already being used in clinical trials for LSDs and other types of leukodystrophies (Penati et al, 2017;Ohashi, 2019;Schiller et al, 2019) and could therefore be adapted to treat children suffering from RNAseT2-deficient leukoencephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapy can be in vivo or ex vivo. In vivo gene therapy directly delivers gene products into the body via systematic or in situ administration (63). Ex vivo gene therapy involves modifying a patient's stem cells externally and then infusing them back into the body.…”
Section: Treatmentmentioning
confidence: 99%
“…Ex vivo gene therapy is in clinical trials for a number of IMDs. Autologous HSCT is part of this procedure as patients receive immunosuppression (Chandler and Venditti 2016;Bernardo and Aiuti 2016), to enable expansion of the transduced host cells, after which the host cells transduced with the desired genetic material are reinfused (Penati et al 2017). Although short-term outcomes of ex vivo gene therapy of clinical trials in various IMDs, such as metachromatic leukodystrophy (Sessa et al 2016) and X-ALD (Cartier et al 2009), have been reported, there were no adults included in these studies to allow comparison of the adult and pediatric outcomes.…”
Section: Autologous Hsct As Prelude To Gene Therapy In Adultsmentioning
confidence: 99%